JURIDICAL ANALYSIS OF THE EMPLOYMENT RELATIONSHIP REGULATION CONCERNING PARENTING BY BABYSITTER - Utama, Gwendolyn Ingrid; Marpaung, Satrya Pangadaran (Yustisia, 2018)
The need for childcare service is a phenomenon in households where parents can not function to nurture children on a full-time basis. Children, especially at the age of golden age, is an "asset" for the nation future because at that age the child absorbs and explores all the basic capabilities of the surrounding environment. Childcare services not only show people who are more mature to the child, but are also expected to be companions who can set a good example and provide a sense of security in meeting the basic needs of children. Childcare services performed by babysitters are ultimately established on the basis of employment relationships with the employer (in general the parents of the child). The working relationship has not been regulated in detailed legislation yet, there are only general guidelines and arrangements through the relevant Minister. For this purpose, the research focuses the problem on the legal policy regarding the working relationship between the babysitter and the employer, and analyzes the ideal arrangements for each party in the working relationship (including employment agencies) in order to create justice for each party. The purpose of this study is to be able to trace each legal policy and generate suggestions for the ideal arrangement in the working relationship that can create justice for every party involved.